2007
DOI: 10.1590/s0004-27492007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Depósito subconjuntival de óleo de silicone após cirurgia vitreorretiniana

Abstract: Ophthalmologists should be aware of this possible complication after intraocular use of silicone oil after vitreoretinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Extraocular migration of emulsified SiO has been reported to occur in the subconjunctival space [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ], [ 6 ], suprachoroidal space [ 7 ], eyelid [ 8 ], orbit [ 9 ], and brain [ 10 ]. Various factors have been implicated in causing the SiO to enter the subconjunctival space following VR surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraocular migration of emulsified SiO has been reported to occur in the subconjunctival space [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ], [ 6 ], suprachoroidal space [ 7 ], eyelid [ 8 ], orbit [ 9 ], and brain [ 10 ]. Various factors have been implicated in causing the SiO to enter the subconjunctival space following VR surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Subconjunctival leakage of silicone oil (SiO) is a known complication following vitreoretinal (VR) surgery. While it may be clinically visible on biomicroscopic examination in around 2.7% of cases [ 1 ], histopathological evidence has shown it to be present in as high as 33% [ 2 ]. In most situations, the leakage is minimal and does not pose many problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular SO migration into the subconjunctival space through a glaucoma tube shunt or through unsutured sclerotomies has been previously reported [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. In this particular case, a sutureless PPV and a pars plana tube GDD coexist, so the question is: Where did the subconjunctival SO come from?…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Some histological studies have confirmed the presence of subconjunctival silicone oil in upto 30% of cases that cannot be detected on routine slit lamp biomicroscopy. 7 Another case series showed that 8-10% patients may have subconjunctival silicone oil bubble after undergoing sutures less 23G vitrectomy. 8 , 9 In the light of these observations, it has been generally recommended not to leave 23G sclerotomy sites without sutures when silicone oil is used as a tamponading agent.…”
Section: Introductionmentioning
confidence: 99%